The Effect of Tai Chi Exercise on Anxiety Disorders of The Elderly - Rahayu, Mifta Amalia Rizka (Confucius Institute Universitas Sebelas Maret, 2023)
Ageing or old age is the final stage in the evolution of the human life cycle that every individual will surely experience. Some diseases start to emerge and are expected at this age; one of them is anxiety disorder. If an older adult has an anxiety disorder, it will affect memory and sleep patterns. This study aimed to find out the impact of Tai Chi gymnastics on anxiety disorders in the elderly in the city of Surakarta. The method used is a qualitative method using relevant journals and reverence. Given the large number of cases of ageing anxiety disorder, there is a need for treatment. Usually, elderly enthusiasts do simple, easy activities like gymnastics in an attempt to heal themselves. Tai Chi exercises are ideally suited to be applied to the elderly because the influence of Tai Chi has proven to be effective in reducing anxiety disorder. Tai Chi exercises usually use circular movements, which are never forced so that the muscles do not feel tense but relax. The results of this study can conclude that Tai Chi exercises are straightforward and suitable for older people as an attempt to treat anxiety disorder.